EFFICACY OF DELONIX REGIA RAFIN (SYN. POINCIANA REGIA BOJER EX. HOOK) FOR POTENTIAL ANTIFUNGAL ACTIVITY - R. A. SHARMA; P. CHANDRAWAT; S. SHARMA; D. SHARMA; B. SHARMA; D. SINGH (The Bioscan, 2010)
Dry powdered materials of flowers and seeds of D. regia were sequentially soxhlet extracted with various solvents to isolate metabolite-rich fractions such as flavonoids, anthraquinones and sterols and also evaluate for antifungal activity against Aspargillus niger, A. flavus, Rhizopus bataticola and Fusarium auxisporum by agar disk diffusion method. In both plant parts, flavonoids showed maximum antifungal activity against A. flavus.